Sifat Fisis Tanah Lempung dengan Penambahan Limbah Serbuk Kulit Kopi - Athaya Zhafirah; Hikmatul Fadilah; Madi Hermadi; Rudy Febrijanto (Institut Teknologi Garut, 2025)
Coffee skin waste is waste obtained from the coffee fruit management process. Piling up coffee skin waste can pollute the environment, but it contains cellulose that can absorb water. This research aims to analyze the effect of the addition of coffee skin powder waste on the physical properties of clay soil in order to improve its quality as a construction and geotechnical material. The research method used experimental tests on the physical properties of clay soil, including moisture content, sieve analysis, content weight, specific gravity, and Atterberg limits. The variation of the addition of coffee skin powder waste was 0%, 10%, 20%, 30%, 40%, and 50% of the soil weight. The results showed that the addition of coffee husk waste caused a decrease in moisture content from 64% to 44.89%, content weight from 1.185 grams/cm3 to 0.677 grams/cm3, and soil specific gravity from 2.6 to 2.28. The plasticity index value also decreased from 26.68 to 18.15, indicating an improvement in soil characteristics. In addition, the proportion of fine grains decreased, while coarse grains increased based on sieve analysis. These results are useful in the geotechnical field to improve soil stability and reduce its plasticity, and in the construction field to improve the bearing capacity of subgrade soils, so they have the potential to be applied in various civil and environmental engineering projects.